Corporate Governance and Audit Report Lag in Non-Financial Companies on the Indonesia Stock Exchange - Sudradjat, Sudradjat; Mai, Muhamad Umar (Universitas Syiah Kuala, 2022)
Purpose This study aims to examine the effect of corporate governance on audit report lag. Corporate governance is proxied by the variable board of directors size, independent board of commissioners, female board of directors, external auditor reputation (Big 4), and audit committee size. The sample of this research is manufacturing companies that are listed consecutively on the Indonesia Stock Exchange during the period 2014 to 2020.Design/Methodology The results of data collection indicate that the sample that meets the criteria is 86 firm-years, or 602 observations. The data analysis method used panel data regression.Results The results showed that the board of directors size, Big 4, and audit committee size had a negative effect on the Audit Report Lag (ARL). Furthermore, the independent board of commissioners has a positive effect on ARL, while the female board of directors has no effect on the Audit Report Lag (ARL).Contribution This research contributes to the development of corporate governance theory in relation to audit report lag. The results of this study can add insight and direction to reduce audit report lag for regulators, management, and investors on the Indonesia Stock Exchange, especially for manufacturing companies.